(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
It is with great pleasure that we present this themed edition of the Journal of the Federal Regional Court of the Third Region on "COMBATING PEOPLE TRAFFICKING". The issue brings together a collection of articles by excellent authors, all of whom have vast experience in combating this crime, which is as silent as it is cruel. I offered my humble contribution with an article, simply expressing the opinion of someone who learns from others. In fact, the importance of this issue lies in shedding light on this complex web of human trafficking, its ramifications, its various aspects and dilemmas. I think we have succeeded. May this be another step towards raising society’s awareness that human trafficking exists, that it is intense, that it is very lucrative and that it is closer to us than we can imagine - as closer as our dreams, needs and desires for a better life are. Translated with DeepL.com (free version)